Preoperative and Postoperative N-terminal Pro B-type Natriuretic Peptide Levels Predict Cardiac Morbidity and Mortality in Patients Undergoing Colorectal Cancer Resection - Haney, Youssef; Enrique, Collantes; James, Hunter; Julie, Stinson; Steve, Smith; Nigel, Stallard; Martin, Been; Ling, Wong (Journal of Colon And Rectal Cancer, 2019)
Introduction: Cardiac complications are a major cause of perioperative morbidity and mortality in patients undergoing colorectal cancer surgery. A quick and reliable system for predicting postoperative cardiac morbidity is needed to predict cardiac events in order to improve outcome in surgery. The aim of this study was to investigate the role of the biochemical marker NT-proBNP in the prediction of postoperative all-cause mortality, cardiac-related mortality and cardiovascular events in patients undergoing colorectal cancer resections. Methods: 100 consecutive patients undergoing colorectal cancer surgery were prospectively recruited. Blood samples were taken preoperatively, 24h, 48h and 5-7 postoperative days to measure NT-proBNP levels. The predictive power of NT-proBNP levels was assessed using Receiver Operating Characteristics (ROC) curves. Results: Cardiac-related morbidity and mortality was 9%. Of eleven deaths, 5 were cardiac-related. Preoperative NT-proBNP was a good predictor of death with ROC area under curve (AUC) of 0.83 (95% C.I. 0.673, 0.993) a strong predictor of cardiac death with AUC of 0.914 (95% C.I. 0.823, 1.000) and a good predictor of cardiac complications with AUC of 0.875 (95% C.I. 0.757, 0.993). NT-proBNP levels 24 hours and 48 hours postoperatively were also strongly predictive of postoperative cardiac morbidity and mortality. Conclusion: Pre- and postoperative NT-proBNP have a role in predicting postoperative death and cardiac complications. This may have significant implications in the planning of postoperative care for high-risk patients.
Keywords: NT-proBNP